On the Generalization of Intergroup Contact: A Taxonomy of Transfer Effects. (October 2019) - Meleady, Rose; Crisp, Richard J.; Hodson, Gordon; Earle, Megan
The contact hypothesis proposes that bringing groups together under favorable conditions can improve intergroup relations. It is now well established that intergroup contact can improve attitudes not only toward the out-group as a whole but also toward other, noncontacted groups ( secondary transfer effect ). We review evidence of a further, higher-order generalization effect whereby intergroup contact also impacts more general cognitive processes outside of the intergroup context (i.e., tertiary transfer effects ). We present a taxonomy of transfer effects that explains these generalization effects as distinct outcomes of the contact process yet contingent on the same component process, specifically, the assessment of the semantic distance between the target (e.g., contacted individual) and the frame (e.g., group prototype). This conceptualization provides an explanatory framework for uniting the disparate forms of transfer effect in the contact literature, clarifying why primary and secondary transfer effects are facilitated by low semantic distance and why contact is more cognitively demanding under conditions of high semantic distance, but with greater potential for cognitive growth.